Numerical and experimental study of the drying of bi-component droplets under various drying conditions - Grosshans, Holger; Gutheil, Eva (International journal of heat and mass transfer, 2016)
This paper presents a combined experimental and numerical study of the evaporation and solid layer formation of single bi-component mannitol-water droplets in hot air. Experimentally, the process of droplet evaporation and drying is studied in a custom-built acoustic levitator. The experimental results are compared with numerical simulations of spherically symmetric bi-component droplets in an unsteady, one-dimensional configuration. The model includes evaporation and solid layer formation. This approach enables the comparison of the temporal variation of the droplet size and the porosity, which are related to the final particle sizes. The study is performed for various drying conditions and initial droplet sizes as well as compositions of the droplets. The objective of this paper is the derivation and validation of a suitable model to predict the properties of spray-dried mannitol particles, depending on their drying conditions. A design of experiments (DoE) is used to define suitable drying conditions and to analyze the results. The study includes initial droplet diameters varying from 350 μm to 550 μm and initial mannitol mass fractions in water droplets ranging from 5% to 15%. The surrounding air temperature is varied from 80 °C to 120 °C. Additionally, different relative humidity of the surrounding air between 1% and 7.5% is studied. Based on the DoE, correlations for results from both experiments and simulations including the temporal evolution of the droplet surface area and the final particle size are derived and discussed. Major influences are identified that dominate particle drying characteristics.